The Influence of Job Placement and Competence Mediation of Job Satisfaction in Increasing the Performance of State Civil Apparatus in Industrial and Trade Services of The Province of Bali - Adhi Dwiswara, Gde Made; Sudja, I Nengah; Dwi Widyani, A.A. (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to determine the effect of Job Placement and Competence on Job Satisfaction in Improving the Performance of State Civil Servants at the Office of Industry and Trade of the Province of Bali. This research was conducted at the Office of Industry and Trade of the Province of Bali with a total sample of 84 people using the saturated or total sampling method. Data collection using a questionnaire. All data obtained from the distribution of questionnaires is feasible to use, then analyzed using variant-based Structural Equation Modeling (SEM) known as Partial Least Square (PLS) analysis. The results showed that (1) Work Placement has a positive and significant effect on Job Satisfaction, (2) Competence has a positive and significant effect on Job Satisfaction, (3) Work Placement has a positive and significant effect on Performance, (4) Competence has a positive and significant effect on Performance, (5) Job Satisfaction has a positive and significant effect on Performance, (6) Job Satisfaction can mediate the effect of Job Placement on Performance, (7) Job Satisfaction can mediate the influence of Competence on ASN Performance at the Bali Provincial Industry and Trade Service ASN.